Is GW170817 a multimessenger neutron star-primordial black hole merger?. Issue 10 (11th October 2021) - Tsai, Yu-Dai; Palmese, Antonella; Profumo, Stefano; Jeltema, Tesla
Abstract: We investigate the possibility of the gravitational-wave event GW170817 being a light, solar-mass black hole (BH) — neutron star (NS) merger. We explore two exotic scenarios involving primordial black holes (PBH) that could produce such an event, taking into account available observational information on NGC 4993. First, we entertain the possibility of dynamical NS-PBH binary formation where a solar-mass PBH and a NS form a binary through gravitational interaction. We find that while dynamical NS-PBH formation could account for the GW170817 event, the rate is highly dependent on unknown density contrast factors and could potentially be affected by galaxy mergers. We also find that PBH-PBH binaries would likely have a larger merger rate, assuming the density contrast boost factor of an order similar to the NS-PBH case. These exotic merger formations could provide new channels to account for the volumetric rate of compact-object mergers reported by LIGO/Virgo. Secondly, we consider the case where one of the NS's in a binary NS system is imploded by a microscopic PBH. We find that the predicted rate for NS implosion into a BH is very small, at least for the specific environment of NGC 4993. We discuss how our analysis can be applied to similar existing (GW190425 and GW190814) and future observations.